The uneven regional pattern of ecological capital in Indonesia: A political economy perspective - Samudro, B.; Bloch, H.; Salim, Ruhul (Inderscience Publishers, 2015)
This study investigates the regional pattern of ecological capital in Indonesia through the principles of political economy. In this discourse, the gap between biocapacity and ecological footprint at the regional level (provinces) indicates the difficulties of environmental sustainability. Unevenness in ecological capital patterns occurs in Indonesian provinces as the gap between biocapacity and ecological footprint is heterogeneous. To demonstrate the causes of this unevenness, the regional pattern of ecological capital is scrutinised using the principle of hegemony, the principle of Circular and Cumulative Causation (CCC) and principle of contradiction.